Őslakos népek Európában? - Az európai emberi jogvédelmi mechanizmus őslakos népekkel kapcsolatos joggyakorlatának aktuális kérdései - Marinkás, György (Debreceni Jogi Műhely, 2015)
The aim of the current study is to examine the jurisprudence of the European Human Rights Mechanism (hereafter: EHRM), focusing on the three most common issues that indigenous peoples living on the European Continent has to face. First, the modern economic activities, which affect their traditional livelihoods. Second, the difficulties of proving their land claims due to the unwritten nature of their culture. Finally, the threat of relocation, which causes severe problems considering their close links to the traditionally occupied lands. Regarding the first issue the author examines how the EHRM developed its jurisprudence from the initial negative attitude of the European Commission on Human Rights (hereafter: ECHR) – which ceased to exist in 1998 – to the more receptive attitude of the European Court of Human Right (hereafter: ECtHR). The main question regarding the second issue is the ability of the EHRM to accept the laws and traditions of a significantly different society as equal. Until the recent times, the ECtHR – and former ECHR – only accepted written proof as authentic. Last, but not least the author introduces three cases in which indigenous peoples had been removed from their ancient lands,  and have not been allowed to return ever since. Considering their close relation with their lands – which serves as basis of cultural identity for them – the result is devastating.Having regard to the above mentioned jurisprudence, three questions arise. First, has the jurisprudence of the EHRM evolved over the years; second – which forecasts the answer for the first question – why does granting effective protection for indigenous peoples still cause problems to the ECtHR? Third, are there any signs of change in the jurisdiction? The answer is complex: the jurisprudence of the ECtHR is definitely evolved; however it still does not reach the level of protection offered by the Inter-American System, which acts as a pioneer on the field of protecting indigenous rights, closely followed by the African System. The attitude of the EHRM is mainly attributable to historical and social reasons creating serious obstacles for the ECtHR. Considering the example of the Inter-American and the African Systems the main question is whether the judges of the ECtHR and the policy makers have the determination to exceed these barriers.